Self-reported tuberculosis in India: evidence from NFHS-4 - Mazumdar, Sumit (BMJ Glob Health, 2019)
This paper reports self-reported levels and socioeconomic patterns in the distribution of tuberculosis (TB) cases in India, based on information collected under the National Family Health Survey-Round 4 (NFHS-4, 2014–2015). Based on a nationally representative sample of over 600 000 households comprising of about 2.9 million individuals, we estimate a self-reported point prevalence of 304 TB cases per 100 000 population, with a higher burden evident among households with poorer wealth status and among individuals with low educational levels. About 55% of the reported TB cases sought treatment from public services, with higher public service use observed in West Bengal, Kerala and Tamil Nadu. However, more than a third of the patients from poorest groups sought treatment from private sources. Results indicate a significant proportion of the general population, including those with completed school-level education continue to have incomplete knowledge on the routes of the spread of TB infection. Social stigma, such as reluctance to disclose about a family member being infected with the disease to others, also remains high. Imminent need for appropriate policy mechanisms for involving the private sector and raising consciousness through suitable advocacy measures is re-emphasised.